Gesture of Agoes Ali Masyhuri in Islamic Congregational Study in Bumi Shalawat Progressive Islamic Boarding School - Razi, Fahrur; Rokhimah, Ilmi Mustafidhah; Melina, Rafika Wahyuni (Proceedings of International Conference on Da'wa and Communication, 2019)
This study focused on Agoes Ali Masyhuri's Gestures in Routine Recitation at the Sidoarjo Progressive Islamic Boarding School. To discuss the focus of the problem, there are several problems that will be answered, namely: (1) How is Gus Ali Masyhuri's body style in routine recitations at the Bumi Sholawat Islamic Boarding School Sidoarjo? To identify these problems, the researcher used a qualitative research whose data analysis principle was descriptive-qualitative, with a subjective approach and the data collection techniques in this study used observation, in-depth interviews, and documentation. While the data analysis technique using data analysis techniques Miles and Huberman models. Conclusions or research results are: The movement style of a preacher during a lecture, in terms of body posture, facial expressions, eyes, and appearance or clothing. During his lecture, Gus Ali was calm and dignified like a father giving advice to his children. When viewed from the expression on his face, Gus Ali always gave a pleasant expression like smiling. Lastly is appearance, Gus Ali always dressed neatly like a cleric and kiai in general, namely using a sarong and koko shirt even Gus Ali used a robe mixed and matched with a turban and white skullcap when the researchers observed and attended his lecture last March 2019. In this study, researchers focused on Gus Ali's body movements in lectures and the meaning of these movements, so in future research it is hoped that they will be able to examine Gus Ali's voice and language style in detail.